In-vitro Bioactivity of Herbal Mixture Curcuma longa Linn, Cissus quadrangularis and Boerhaavia diffusa - An In vitro Study - Dinesh, Y.; Abilasha, R.; Ramani, Pratibha; Kumar, S. Rajesh (Challenges and Advances in Pharmaceutical Research Vol. 3, 2022)
Plants play an essential role in medication development, and the pharmaceutical industry relies largely on natural products to produce new drugs. Curcumin, a natural compound contained in the rhizomes of the plant Curcuma longa Linn, Cissus quadrangularis L. and Boerhaavia diffusa L. are used commonly for their medicinal purposes. The aim of this study is to evaluate the cytotoxic, antioxidant and thrombolytic, antiinflammatory and antimicrobial properties of the aqua-alcoholic extract of the herbal mixture (Curcuma longa Linn +Cissus quadrangularis +Boerhaavia diffusa). Aqua-alcoholic extract of mixture of Curcuma longa Linn, Cissus quadrangularis and Boerhaavia diffusa was prepared. Phytochemical in-vitro studies were done using the CCB mixture cytotoxicity by brine shrimp lethality assay, antioxidant activity by DPPH assay, anti inflammatory activity by albumin denaturation assay, antimicrobial activity against Staphylococcus aureus, Streptococcus mutans, Escherichia coli and Candida albicans by agar well diffusion method, thrombolytic activity by clot lysis assay. In a brine shrimp lethality assay, the CCB mixture demonstrated excellent cytotoxic activity at various concentrations, boosting antioxidant activity with DPPH assay, increasing thrombolytic activity, increasing anti-inflammatory activity, and increasing anti-microbial activity with increasing concentration, but the anti-microbial activity was ineffective as positive controls. The CCB mixture exhibits increased cytotoxic, antioxidant, thrombolytic, anti-inflammatory, and antibacterial activities in this in vitro investigation. More research on in vivo animals and human clinical trials is required.